Islamic Capital Markets and Economic Growth: A Comparative Study of Pakistan, Malaysia and UAE - Dr. Mohammad Ayaz; Dr.Hassan Shakeel Shah; Dr. Talat Hussain; Majid Iqbal (Islamic Banking and Finance Review, 2019)
This research was conducted to find out whether Islamic capital markets (ICMs) have any effect on economic growth (EG). The study also made a comparison between three countries including Pakistan, Malaysia and UAE in this regard. Quantitative research technique was used in this study, where secondary and time series data was collected on a quarterly basis for the period 2009-2017. The effect of independent variables (IVs) on the dependent variable (DV) was examined. Co-integration and ARDL test were applied in Eviews 9 and Microfit 5.0. A growth model was developed for the selected countries separately in order to see whether IVs had any effect on DV. GDP was the DV of study while IMCAP, TNI and TNL were its IVs. It was found that in case of Pakistan and Malaysia, all the IVs had a significant effect on EG in the short run, while in the long run only IMCAP and TNI have a significant impact. In case of UAE, only two IVs (IMCAP and TNL) had a significant effect on EG in the short run, while in long run only one IV (IMCAP) has a significant impact. Further, it was found that IVs jointly had a significant effect on EG of the selected countries. So, this study concluded that ICMs do have a significant effect on EG of Pakistan, Malaysia and UAE. Considering the importance of ICMs in EG, regulators and policy makers are likely to benefit from the results of the current study which acts as a guide for developing and reforming the ICMs of Pakistan, Malaysia and UAE. Keywords: , ,